ANALISIS KETERLIBATAN AYAH DALAM PENGASUHAN ANAK DI SUKU BATAK TOBA DESA UJUNG TANDUK KECAMATAN LAGUBOTI KABUPATEN TOBA SAMOSIR - Sibarani, Zuansi Putra; Risma, Devi; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrak: The background of this research is the problem of father's involvement in childcare in the Toba Batak Tribe of Ujung Tanduk Village, Laguboti Subdistrict, Toba Samosir Regency as seen by the father who gave full child care to the mother, busy father to make a living, every day always went to the tuak shop from afternoon to late at night. This study aims to analyze the involvement of fathers in parenting in the Toba Batak Tribe, Ujung Tanduk Village, Laguboti District, Toba Samosir Regency. The population in this study were fathers in the Toba Batak Tribe, Ujung Tanduk Village, Laguboti Subdistrict, Toba Samosir Regency who had early childhood with a total of 25 fathers. Because of the large population, a portion of the population is sampled, namely 6 people. The sampling technique is by distributing questionnaires to the father. Taking the subject by taking 3 fathers who value good involvement and 3 fathers who value bad involvement. The method used in this study is descriptive qualitative to analyze the involvement of fathers in parenting in the Toba Batak Tribe, Ujung Tanduk Village, Laguboti District, Toba Samosir Regency. Data collection techniques used were interviews, observation, and documentation. Data analysis techniques use qualitative data in the form of a collection of tangible words and not a series of numbers and cannot be arranged in classification categories. Based on the results of interviews with fathers, stated that there was involvement of fathers in parenting. Can be seen from aspects of father's involvement that are quite good. However, there are several aspects of involvement that are not good, for example taking care of children, feeding, and bathing children.Key Words: Father Involvement in Parenting